Effect of potassium titanate fibres and metal sulphides in the tribological behaviour of brake friction composites - Sathickbasha Katharbasha; Hariharasakthisudhan Ponnarengan; Varun Kumar Arulvizhi; Venkata Ramarao Mutyala; Sivakumar Chandramohan (Tribology and Materials, 2024)
In a brake system, brake friction composites are essential for converting kinetic energy into frictional heat. An optimal brake friction composite should ensure a stable coefficient of friction under extreme operational conditions. This study examines the tribological performance of brake friction composites incorporating potassium titanate fibres and metal sulphide lubricants in standard brake pad formulation. Brake friction composites were engineered by varying the potassium titanate fibre content from 10 to 30 %, while the lubricant mixture (comprising graphite, MoS2, Bi2S3 and Sb2O3) was proportionally adjusted from 27 to 7 %, with the filler and binder concentrations held constant throughout the formulation. The phenolic resin-based composites were characterised for their physical, chemical and mechanical properties in accordance with the IS 2742 (Part 4) standard. The tribological performance of the fabricated composites was evaluated using a rotating drum setup, following the SAE J661 procedure. The worn surfaces of the samples were analysed to identify wear mechanisms utilising scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS). The results demonstrated that the optimal combination of potassium titanate fibres and metal sulphide lubricants significantly influences wear resistance and friction stability, with varying degrees of primary and secondary plateau formation observed. This comprehensive characterisation provides valuable insights into the material's behaviour under operational conditions, guiding the development of advanced brake friction composites.